A Chimeric Conjugate of Antibody and Programmable DNA Nanoassembly Smartly Activates T Cells for Precise Cancer Cell Targeting. (25th July 2022) - Tang, Rui; Fu, Yu‐Hao; Gong, Bo; Fan, Ying‐Ying; Wang, Hong‐Hui; Huang, Yan; Nie, Zhou; Wei, Ping
Abstract: Synthetically directing T‐cells against tumors emerges as a promising strategy in immunotherapy, while it remains challenging to smartly engage T cells with tunable immune response. Herein, we report an intelligent molecular platform to engineer T‐cell recognition for selective activation to potently kill cancer cells. To this end, we fabricated a hybrid conjugate that uses a click‐type DNA–protein conjugation to equip the T cell‐engaging antibody with two distinct programmable DNA nanoassemblies. By integrating multiple aptameric antigen‐recognitions within a dynamic DNA circuit, we achieved combinatorial recognition of triple‐antigens on cancer cells for selective T‐cell activation after high‐order logic operation. Moreover, by coupling a DNA nanostructure, we precisely defined the valence of the antigen‐binding aptamers to tune avidity, realizing effective tumor elimination in vitro and in vivo. Together, we present a versatile and programmable strategy for synthetic immunotherapy. Abstract : A chimeric antibody‐nucleic acid T‐cell engager (CAN‐TE) redirecting T cells to precisely target and potently kill the cancer cells by coupling 1) a dynamic DNA circuit with high‐order logic function for smart cell recognition or 2) a multivalent aptameric DNA nanostructure to control the targeting avidity for tunable immune response is reported.